The root of Chinese qigong secrets for health, longevity & enlightenment - Yang, Jwing-Ming 1946 (Wolfeboro, NH YMAA Publication Center, 2022)
Long considered a classic text by teachers and students, "The Root of Chinese Qigong" offers the principles and theories of qigong practice. This third edition includes updated pinyin that includes diacritical tonal marks (for proper pronunciation of Chinese words) and updated Chinese text character font (providing better readability). Dr. Yang is acclaimed for helping readers understand qigong concepts deeper and more clearly by expressing them in familiar methods for the Western mind. He takes these ancient concepts and presents them in a logical way that helps practitioners stay on the right path to deepen knowledge and skill. In this book Dr. Yang teaches sitting and standing meditation, demonstrates qi massage techniques, and examines the Qi pathways in your body. He explains correct breathing methods, shares secrets for quieting the mind, and discusses how to increase your body's qi supply. He further explains important concepts such as the Three Treasures and regulating the body, breath, and mind. Whatever style of qigong you may practice, making sense of qigong theory and principles is the best way of achieving your goals sooner, more accurately, and deeper.--Publisher.
Revision of the 1997 edition.
Includes bibliographical references, translation and glossary of Chinese terms, and index.
Text in English, with some Chinese characters included.
111183
Keywords: Qi gong; Qi gong -- Therapeutic use; Qi (Chinese philosophy); Mind and body; Well-being.; Meditation; Spiritual care (Medical care); Spirituality; Medicine, Chinese; Holistic medicine; Qi; Medicine, Chinese Traditional; Body, Mind, & Spirit / Healing / Energy (Qigong, Reiki, Polarity); Health & Fitness / Tai Chi; Philosophy / Mind & Body; Sports & Recreation / Martial Arts / General